Penerapan Strategi Problem Based Instruction untuk Meningkatkan Prestasi Belajar Siswa Kelas V pada Mata Pelajaran IPA Sains di MIS Al-Yaminy Dompu Tahun Pelajaran 2019/2020 - Runa (Jurnal LENTERA: Jurnal Studi Pendidikan, 2020)
The learning process is always demanded how the teaching materials conveyed by the teacher can be completely mastered by students so that in teaching, especially in Science, an appropriate learning strategy is needed. Teachers should choose the right strategy to facilitate the achievement of effective and efficient learning goals so that student learning outcomes are achieved both from the aspects of knowledge, skills, and attitudes. The purpose of this research is to find out how to implement the Problem Based Instruction Strategy to improve the learning achievement of grade V students in the Science subjects at MIS Al-Yaminy Dompu in the 2019/2020 school year. This classroom action research was conducted in 2 cycles, from the results of the actions taken proved to be able to improve learning achievement in class V. In the first cycle, the students' absorption capacity was 62.71% and classically 47.06% (sufficient category). The percentage of completeness and absorption power has not yet reached the classical level of mastery learning, which is at least 85% and for the absorption capacity> 65%. After the second cycle of action, there was an increase in student absorption by 78.53% and classically 88.24% (very good category). The results of this action research indicate that the application of the Problem Based Instruction Strategy is effective for improving student achievement in science subjects in class V at MIS Al-Yaminy Dompu in the 2019/2020 school year